Mekanisme Pembatalan Peraturan Desa dalam Tinjauan Konstitusi dan Peraturan Perundang-Undangan - Samiah S; Fathorrahman Fathorrahman (Birokrasi: JURNAL ILMU HUKUM DAN TATA NEGARA, 2023)
Village regulations are one of the many types and forms of statutory regulations. As part of legal products in the national legal system, regulations follow the regime of statutory regulations. In the statutory regime, the model for canceling a product that is considered contradictory is with various models. The model is regulated in the constitution, especially regulations whose hierarchy are under the law through the Supreme Court. Does the Perdes annulment model also follow this regime? In this study, the type of research used is normative-juridical with a statutory approach. From this study it can be concluded that the model for canceling village regulations is different from the cancellation regime in general. This is explicitly regulated in the Village Law. The cancellation was not through a court model, but by the agency above it, namely the regent.